Copyright Anxiety and Creative Labor in Indonesian AI-Generated Content Culture, the case: AI Art, AI Voice, AI Music in Indonesia - RR Ella Evrita H; Efridani Lubis (Jurnal Sipakatau: Inovasi Pengabdian Masyarakat, 2026)
The rapid diffusion of generative artificial intelligence (GenAI) has transformed digital cultural production and accelerated the emergence of AI-generated content across platform-based creator economies. In Indonesia, the growth of AI Art, AI Voice, and AI Music on platforms such as TikTok, YouTube, Instagram, Discord, and X has intensified debates over originality, copyright, authorship, and the authenticity of human creativity. Existing studies have predominantly examined these issues from legal, regulatory, and intellectual property perspectives, while paying limited attention to creators’ lived experiences and the cultural implications of AI-mediated production. This study investigates how copyright anxiety is constructed, negotiated, and normalized, and how creative labor is reconfigured within Indonesian AI creator communities. Using a qualitative approach, the research employs critical digital ethnography and digital discourse analysis based on multi-platform observations, public discussions, AI-generated artworks, AI voice covers, AI music remixes, and copyright debates. The findings identify three interconnected dynamics: the emergence of copyright anxiety as a form of cultural insecurity, the intensification of creative precarity through platform-dependent algorithmic production, and the ongoing negotiation of originality and creative legitimacy in AI-mediated cultural production. The study contributes theoretically by conceptualizing copyright as a socio-cultural concern rather than merely a legal issue, and methodologically by demonstrating the value of critical digital ethnography for examining AI-generated content as an everyday cultural practice within Indonesia’s evolving platform society.